2004
DOI: 10.1038/sj.bjc.6601753
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing time from presentation to treatment of colorectal and breast cancer in urban and rural areas

Abstract: Stage at diagnosis and survival from cancer vary according to where people live, suggesting some may have delays in diagnosis. The aim of this study was to determine if time from presentation to treatment was longer for colorectal and breast cancer patients living further from cancer centres, and identify other important factors in delay. Data were collected on 1097 patients with breast and 1223 with colorectal cancer in north and northeast Scotland. Women with breast cancer who lived further from cancer centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
6
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 16 publications
6
76
6
3
Order By: Relevance
“…For NHL, age was an important factor. For breast cancer, marital status and ethnic group were important factors, again strengthening the current evidence base (Tartter et al, 1999;Nosarti et al, 2000;Thongsuksai et al, 2000;Arndt et al, 2002;Meechan et al, 2002;Gwyn et al, 2004;Robertson et al, 2004). The trends in the associations using both statistical approaches were all in the same direction for each of the six cancers.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…For NHL, age was an important factor. For breast cancer, marital status and ethnic group were important factors, again strengthening the current evidence base (Tartter et al, 1999;Nosarti et al, 2000;Thongsuksai et al, 2000;Arndt et al, 2002;Meechan et al, 2002;Gwyn et al, 2004;Robertson et al, 2004). The trends in the associations using both statistical approaches were all in the same direction for each of the six cancers.…”
Section: Discussionsupporting
confidence: 54%
“…The GLM showed that the significant factors varied by cancer type. Looking at total delay, for colorectal, age, and marital status were the key factors in explaining the variation in delays; this strengthens the limited evidence base to date (Langenbach et al, 2003;Gonzalez-Hermoso et al, 2004;Robertson et al, 2004). For lung and ovarian cancer, none of the factors stood out as being important.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In a recent issue, Robertson et al (2004) reported on the time from presentation to treatment of colorectal and breast cancers in Scottish urban and rural areas.…”
Section: Sirmentioning
confidence: 99%